Multiple Fungi May Connect the Roots of an Orchid (Cypripedium reginae) and Ash (Fraxinus nigra) in Western Newfoundland - Weerasuriya, Nimalka M.; Kukolj, Katarina; Spencer, Rebecca; Sveshnikov, Dmitry; Thorn, R. Greg (Frontiers in Fungal Biology, 2022)
Showy lady's slipper (Cypripedium reginae Walter, Orchidaceae) and black ash (Fraxinus nigra Marshall, Oleaceae) often co-occur in close proximity in fens in western Newfoundland, Canada. Metabarcoding of DNA extracted from root samples of both species following surface sterilization, and others without surface sterilization was used to determine if there were shared fungal endophytes in the roots of both species that could form a common mycorrhizal network between them. A wide variety of fungi were recovered from primers amplifying the nuclear ribosomal internal transcribed spacer region (ITS2). Sixty-six fungal sequences were shared by surface-sterilized roots of both orchid and ash, among them arbuscular mycorrhizal fungi (Claroideoglomus, Dominikia, Glomus and Rhizophagus), ectomycorrhizal fungi (Inocybe and Tomentella), the broad-host root endophyte Cadophora orchidicola, along with root pathogens (Dactylonectria, Ilyonectria, Pyricularia, and Xylomyces) and fungi of unknown function. There appear to be multiple fungi that could form a common mycorrhizal network between C. reginae and F. nigra, which might explain their frequent co-occurrence. Transfer of nutrients or carbon between the orchid and ash via one or more of the shared fungal endophytes remains to be demonstrated.